Does study counselling foster STEM intentions andreduce the STEM gender gap? Evidence from a randomized controlled trial - Beckmann, Janina [Verfasser]; Fervers, Lukas [Verfasser] (My University, 2024)
„Low interest in STEM (science, technology, engineering and mathematics) among high school students in general and women in particular is a highly prevalent phenomenon in many industrialized countries. This study analyses whether study counselling – guiding students to select a major in higher education through self-exploration and fostering their confidence in completing higher education – increases their aspirations toward STEM. We pay particular attention to gender differences in this association. To identify the causal impact of the intervention, we employ a Randomized Controlled Trial (RCT) with pre-post design. Our results show that students participating in the counselling intervention more frequently develop aspirations toward life and environmental sciences subjects such as biology. Moreover, this effect is stronger for female students. In light of these results, we discuss the potential role of study counselling in reducing gender segregation in higher education.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 6.3.1 Ingenieurberufe, Chemiker, Physiker, Mathematiker; L 5 Beratung & Orientierung; S 1.4 Hochschulbildung; G 2.4.5 Gender Mainstreaming; 370; 300; MINT-Berufe; Attraktivität; Attraktivität; Studienberatung; Einflussfaktor; Studienfachwahl; Geschlechtsspezifische Faktoren; Geschlechtersegregation